Severe drought changes the soil bacterial community in wetland ecosystem: Evidence from the largest freshwater lake wetland in China - Zhao, Jun; Shu, Wang; Wang, Lachun; Zhang, Xueli (Limnologica, 2022)
The Poyang Lake, the largest freshwater lake in China, is subject to drastic seasonal hydrological fluctuations due to the global climate change and human activities, resulting in the unclear impact of soil bacterial communities undergoing severe drought pressure. To elucidate this, soil samples were collected in Phragmites, Carex, and Phalaris, and were incubated in the laboratory under three moisture levels: 30% WHC (maximum water-hold capacity) representing severe drought, 50% WHC representing moderate drought, and 80% WHC representing suitable moisture conditions. Soil bacterial communities were profiled by the 16 S rRNA gene using the Illumina high-throughput sequencing technique. The results showed that the Shannon–Wiener index of bacterial communities decreased with the decrease of soil moisture. The Chao1 index decreased with the decrease of soil moisture in the Carex and Phalaris zone soils, while the index first decreased and then increased in the Phragmites zone soil. The Shannon–Wiener index was significantly different among the three dry-wet conditions (p = 0.017), whereas the Chao1 index was not (p = 0.813). Drought altered the relative abundance of different bacterial phyla. With the decrease of soil moisture, the relative abundance of Actinobacteria increased, whereas the relative abundance of Proteobacteria, Chloroflexi, Acidobacteria, and Nitrospirae decreased. LEfSe analysis showed that the number of differential species in the soil of different vegetation zones (n = 57) was significantly higher than the number of differential species under different drought conditions (n = 13). Overall, the difference of soil properties in different vegetation zones has a greater effect on the bacterial community structure than that of different drought conditions in Poyang Lake wetland. This study enriched our knowledge of the drought conditions impact of bacterial communities on server drought lake ecosystems.